The return of the king : - Tolkien, J. R. R. (John Ronald Reuel) (Houghton Mifflin, 2003)
"The story moves on with a tremendous narrative rush to its climax... extraordinarily imaginative work, part saga, part allegory, and wholly exciting." Daily Telegraph